ALGORITMA DJIKTRA UNTUK MENENTUKAN JALUR TERPENDEK PADA DISTRIBUSI AIR MINERAL - Muhammad Sadli (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2015)
Implementation issues determine the shortest route to the water distribution using the algorithm Djiktra. Distribution of mineral water is emphasized in the search by using the shortest path, which will look for some alternative solutions to the completion of a more effective and efficient. problems during this time is crossed by the shortest path to get to the destination, or whether it can keep costs to a minimum and also whether it can reduce the travel time to be traversed. Results of algorithm implementation Djiktra here to show where the optimum route. Paths are achieved by using the shortest path 21 cities input is: [the city of Lhokseumawe, Kab. North Aceh district. East Aceh, Langsa, Kab. Aceh Tamiang, Kab. Gayo Lues, Kab. Southeast Aceh, City Subussalam, Kab. Singkil, Kab. South Aceh District. Southwest Aceh district. Central Aceh district. Nagan Raya, Kab. West Aceh District. Aceh Jaya, Banda Aceh, Kota Sabang, Kab. Aceh Besar, Kab. Pidie district. Pidie Jaya district. Bireun. By using the search algorithm generates Djiktra route: [Kota Lhokseumawe, Kab. North Aceh district. East Aceh, Langsa, Kab. Aceh Tamiang, Kab. Gayo Lues, Kab. Southeast Aceh, City Subussalam, Kab. Singkil, Kab. South Aceh District. Southwest Aceh district. Central Aceh district. Nagan Raya, Kab. West Aceh District. Aceh Jaya, Banda Aceh, Kota Sabang, Kab. Aceh Besar, Kab. Pidie district. Pidie Jaya district. Bireun] with a total distance of 2255 kilometers and when input other cases the number of input the city as many as 21 cities also will produce different distances. Djiktra algorithm is an algorithm to determine the shortest path.